An Overview on the Potential Hazards of Pyrethroid Insecticides in Fish, with Special Emphasis on Cypermethrin Toxicity - Mayada R. Farag; Mahmoud Alagawany; Rana M. Bilal; Ahmed G. A. Gewida; Kuldeep Dhama; Hany M. R. Abdel-Latif; Mahmoud S. Amer; Nallely Rivero-Perez; Adrian Zaragoza-Bastida; Yaser S. Binnaser; Gaber El-Saber Batiha; Mohammed A. E. Naiel (Animals, 2021)
Pesticides are chemicals used to control pests, such as aquatic weeds, insects, aquatic snails, and plant diseases. They are extensively used in forestry, agriculture, veterinary practices, and of great public health importance. Pesticides can be categorized according to their use into three major types (namely insecticides, herbicides, and fungicides). Water contamination by pesticides is known to induce harmful impacts on the production, reproduction, and survivability of living aquatic organisms, such as algae, aquatic plants, and fish (shellfish and finfish species). The literature and information present in this review article facilitate evaluating the toxic effects from exposure to various fish species to different concentrations of pesticides. Moreover, a brief overview of sources, classification, mechanisms of action, and toxicity signs of pyrethroid insecticides in several fish species will be illustrated with special emphasis on Cypermethrin toxicity.